SOSIALISASI DAN MITIGASI BENCANA LETUSAN GUNUNG API PADA ANAK-ANAK DESA PURI KELOD BANJAR MANDALA SARI DENPASAR TIMUR - Nia Maharani; Evi Dwi Krisna; I Made Dedy Setiawan (Lembaga Penelitian dan Pengabdian Masyarakat (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2023)
One of the natural disasters that often occurs in Indonesia is volcanic eruptions. This natural phenomenon cannot be predicted exactly when it will occur. Volcanic eruptions can cause loss and death. Indonesia is one of the countries that is not spared from volcanic eruptions due to its geographical location. There have been many recorded volcanic eruptions in Indonesia, including in the province of Bali. Anticipating volcanic eruption disasters can be done to reduce the impact of large losses. One of them is through socialization activities about volcanic eruptions among children carried out by the PKM team in Banjar Mandalasari, East Denpasar District. Based on interviews with children at the beginning, there was no socialization about the volcanic eruption disaster that they received either at school or in the area where they lived. Children are state assets, don't let children become victims of volcanic eruptions. The future is still long. The results of the questionnaire given before the PKM activity showed that children still lack basic knowledge about volcanoes and their dangers.